2011
DOI: 10.1039/c1cc00079a
|View full text |Cite
|
Sign up to set email alerts
|

Coordination polymer nanorods of Fe-MIL-88B and their utilization for selective preparation of hematite and magnetite nanorods

Abstract: Coordination polymer nanorods are synthesized from the hexagonal 3D structure of Fe-MIL-88B. Subsequently, hematite (α-Fe(2)O(3)) and magnetite (Fe(3)O(4)) nanorods are selectively prepared by controlling the calcination conditions of coordination polymer nanorods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
134
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(147 citation statements)
references
References 34 publications
12
134
0
Order By: Relevance
“…Thus, MOF crystal engineering is of utmost importance not only for MOF applications but also to improve the performance of other functional materials that can be derived from them and in which particle size and morphology will also play a key role. Cho et al [293] reported the synthesis of α-Fe 2 O 3 particles by a two-step calcination of MIL-88-Fe as sacrificial hard template [293,296]. As shown in Figure 43, the MOF morphology was retained after calcination and the resulting iron oxide is composed of aggregated 20 nm-sized nanoparticles, between which non-ordered mesopores are formed.…”
Section: Applicationsmentioning
confidence: 95%
“…Thus, MOF crystal engineering is of utmost importance not only for MOF applications but also to improve the performance of other functional materials that can be derived from them and in which particle size and morphology will also play a key role. Cho et al [293] reported the synthesis of α-Fe 2 O 3 particles by a two-step calcination of MIL-88-Fe as sacrificial hard template [293,296]. As shown in Figure 43, the MOF morphology was retained after calcination and the resulting iron oxide is composed of aggregated 20 nm-sized nanoparticles, between which non-ordered mesopores are formed.…”
Section: Applicationsmentioning
confidence: 95%
“…[7][8][9][10] Due to their modular nature and structural tunability, application of MOFs has been widening in the fields of light harvesting, [11][12][13][14][15] sensing, 16 optical luminescence, 17,18 ionic conductivity, [19][20][21] nonlinear optical behavior 22 and as precursors for the synthesis of nanomaterials with interesting properties. [23][24][25][26][27][28][29] A huge variety of MOFs have been synthesized and reported so far with synthesis techniques such as hydrothermal, solvothermal, microwave assisted heating, mechanochemical, electrochemical and, more recently, ultrasonic processes. 30 Ni-BTC, as a part of this long chain of MOFs, has been initially reported by Yaghi. 31 constructed by btb linkers (btb = benzene 1,3,5-tribenzoate) and {Ni 5 (µ 3 -O) 2 (O 2 C) 6 }, porous paddle-wheel structures using different combination of metal/organic linker/base/solvents via high throughput synthesis 33 and CPO-27(Ni) 34 are few other noticeable contributions to Ni based porous solids.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MOFs are proved to be ideal sacrificial templates for the synthesis of metal oxides via thermal decomposition because of their unique long-range ordering structure and porosity compared to other sacrificial templates [32][33][34][35][36][37][38]. For instance, CuO/Cu 2 O hollow polyhedrons with porous shells obtained directly from calcination of MOF exhibit excellent cycle performance and enhanced lithium storage capacity [39].…”
Section: Introductionmentioning
confidence: 98%